(untitled) (Research, Society and Development, 2020)
Murici and gabiroba fruits are common in the Brazilian Cerrado, but their consumption is limited not only by the region, but also because they are seasonal and perishable fruits. Thus, this work was intended to characterize physically, chemically, nutritionally and anti-nutritionally the peel, pulp and seed fractions for use, by the food industry, of whole fruits or their fractions. Analyzes of horizontal, transversal diameter and mass were carried out on the whole fruits, and on the fractions the following analyzes (Aw, color, soluble solids, pH, titratable acidity, moisture, protein, lipids, ash, carbohydrates, caloric value, antioxidants (DPPH, FRAP, and phenolics), vitamin C, cyanogen compounds, phytates and tannins, where the results obtained were tabulated and presented together with standard deviation and an analysis of variance in the averages was carried out. The results showed that in both fruits and, depending on their fractions , significant levels of protein and vitamin C are found, in addition to having antioxidant activity In the skins and seeds of murici and gabiroba fruits, there were no levels of protease inhibitors, cyanogenic glycosides, nor phytates; the presence of tannins does not compromise use in human food, only care is needed when incorporating and ingesting foods rich in calcium Therefore, the insertion of the peel, pulp and seed fractions of the murici and gabiroba fruits in food products is viable, contributing to adding value and helping to reduce organic waste.